La distanciation dans l’œuvre régionaliste de Grant Wood comme moyen de mise en échec du nationalisme - Kamila Benayada (Revue LISA)
Regionalist painter Grant Wood’s works complied with much of the regionalist ideology as defined by critic Thomas Craven with its nationalism and its rejection of European Modernism. Wood displayed his concern for an American idiom in many of his works. However, while they use pictorial elements that suggest acceptance of the nationalist rhetoric of both Craven and the New Deal art projects, Wood’s works actually show aesthetic preoccupations similar to those of Modernists, and a growing distance from the mythic representations of America often found in regionalist art. While Wood empathises with his countrymen, he also introduces elements within the narrative, and aesthetic elements, that contradict his acceptance of the dominant discourse. Strange, inappropriate and unexpected incursions question the theme and aesthetic affiliation of a work. This deviation, this escape from the frame imposed by Craven and the New Deal, this estrangement, can work as a questioning of America, its values, its myths and its self-representation.